Characterization of Nasco grape pomace-loaded nutriosomes and their neuroprotective effects in the MPTP mouse model of Parkinson’s disease - Parekh, Pathik; Serra, Marcello; Allaw, Mohamad; Perra, Matteo; Marongiu, Jacopo; Tolle, Giulia; Pinna, Annalisa; Casu, Maria Antonietta; Manconi, Maria; Caboni, Pierluigi; Manzoni, Olivier J. J.; Morelli, Micaela (Frontiers in Pharmacology, 2022)
Grape pomaces have recently received great attention for their richness in polyphenols, compounds known to exert anti-inflammatory and antioxidant effects. These pomaces, however, have low brain bioavailability when administered orally due to their extensive degradation in the gastrointestinal tract. To overcome this problem, Nasco pomace extract was incorporated into a novel nanovesicle system called nutriosomes, composed of phospholipids (S75) and water-soluble maltodextrin (Nutriose® FM06). Nutriosomes were small, homogeneously dispersed, had negative zeta potential, and were biocompatible with Caco-2 cells. Nasco pomace extract resulted rich in antioxidant polyphenols (gallic acid, catechin, epicatechin, procyanidin B2, quercetin). To investigate the neuroprotective effect of Nasco pomace in the subacute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of Parkinson’s disease (PD), Nasco nutriosomes or Nasco suspension was administered intragastrically and their neuroprotective effects were evaluated. Degeneration of nigro-striatal dopaminergic neurons induced by subacute MPTP treatment, the pathological hallmark of PD, was assessed through immunohistochemical evaluation of tyrosine hydroxylase (TH) in the caudate-putamen (CPu) and substantia nigra compacta (SNc), and the dopamine transporter (DAT) in CPu. Immunohistochemical analysis revealed that Nasco nutriosomes significantly prevented the reduction in TH- and DAT-positive fibres in CPu, and the number of TH-positive cells in SNc following subacute MPTP treatment, while Nasco suspension counteracted MPTP toxicity exclusively in SNc. Overall, these results highlight the therapeutic effects of Nasco pomace extract when administered in a nutriosome formulation in the subacute MPTP mouse model of PD and validate the effectiveness of the nutriosome preparation over suspension as an innovative nano-drug delivery system for in vivo administration.